Description of the final instar nymphs of seven species from Anacroneuria Klapálek (Plecoptera: Perlidae) in Costa Rica, and first record for an additional genus in Central America - Gutiérrez-Fonseca, Pablo E.; Springer, Monika (Zootaxa, 2011)
The final nymphal stages for seven species of Anacroneuria Klapálek from Costa Rica are described for the first time based upon reared specimens: A. benedettoi Stark, 1998, A. divisa (Navás, 1924), A. holzenthali Stark, 1998, A. lineata (Navás, 1924), A. marca Stark, 1998, A. perplexa Stark, 1998 and A. varilla Stark, 1998. Illustrations are provided for all important morphological characters and distinguishing characters are discussed. Distribution maps for each species are provided and remarks on the ecology are included. Finally, an additional genus is recorded for Central America for the first time, from two nymphs collected from the Central Valley in Costa Rica, possibly belonging to the genus Perlesta.